Screening of visuospatial abilities in amyotrophic lateral sclerosis (ALS): a pilot study using the battery for visuospatial abilities (BVA) - Minoo Sharbafshaaer; Mattia Siciliano; Carla Passaniti; Valeria Sant’Elia; Marcello Silvestro; Antonio Russo; Sabrina Esposito; Gioacchino Tedeschi; Luigi Trojano; Francesca Trojsi (Orphanet Journal of Rare Diseases)
Abstract Background Cognitive deficits related to frontotemporal dysfunction are common in Amyotrophic Lateral Sclerosis (ALS). Visuospatial deficits, related to posterior cerebral regions, are often underestimated in ALS, though they play a crucial role in attending daily living activities. Our pilot study aims at assessing visuospatial abilities using a domain-specific tool in ALS patients compared to healthy controls (HC). Methods Twenty-three patients with early ALS and 23 age- and education-matched HC underwent the Battery for Visuospatial Abilities (BVA), including 4 visuo-perceptual and 4 visuo-representational subtests. Results When compared to HC, ALS scored worse in 2 visuo-perceptual subtests (i.e., Line Length Judgment and Line Orientation Judgment) and 1 visuo-representational tasks (i.e., Hidden Figure Identification, HFI) (p < 0.01). No correlations arose between ALS clinical features and BVA performance. More than 80% of the ALS cohort obtained abnormal scores in the HFI subtest. Conclusions Our findings revealed that patients with ALS scored worse (compared to HC) on selective tests tapping “perceptual” and “representational” visuospatial abilities, since the early stages of disease. In clinical practice, our findings highlight the need for multi-domain neuropsychological assessment, for monitoring disease courses and properly organizing care management of patients with ALS.